Detection of chromogranin in neuroendocrine cells with a monoclonal antibody. - Wilson, B. S. (1984)
A monoclonal antibody ( LK2H10 ) produced against a human pheochromocytoma reacted immunohistochemically with 126 normal and neoplastic endocrine tissues with secretory granules which were formalin-fixed and paraffin-embedded. Antibody LK2H10 did not react with 46 other endocrine tissues or tumors without secretory granules nor with 113 normal and neoplastic nonendocrine cells and tumors. Tumors with abundant secretory granules showed intense and diffuse staining, and tumors with few granules, such as Merkel cell carcinomas, neuroblastomas, and small cell carcinomas of lung, showed focal staining. Antibody LK2H10 did not react with melanomas, nevi, posterior pituitary, peripheral nerve tissues, or neurons. The target structure of LK2H10 was identified as human chromogranin, of which the major fraction was chromogranin A (mol wt 68,000 daltons). Preabsorption with purified chromogranin A blocked immunoperoxidase staining by LK2H10 in normal adrenal medulla, in the anterior pituitary, and in a pheochromocytoma. Ultrastructural immunohistochemistry with LK2H10 showed that chromogranin was present in cytoplasmic secretory granules. These results indicate that chromogranin is widely distributed in the secretory granules of most polypeptide-producing endocrine tissues, and it is readily detected with the use of monoclonal antibody LK2H10 . The detection of this marker can be very helpful as a diagnostic aid for neuroendocrine cells and tumors.